A review of microplastics measuring methods in water and wastewater bodies - Hamze Sharifi (Tehran University of Medical Sciences, 2021)
Background and Objective: Recently, microplastics (MPs) have been found in the aquatic and terrestrial environments, air, and food. Other pollutants can be transported by MPs and pose a threat to the human, animal, and environment. Measurement and evaluation of microplastics can either increase knowledge about them or boost understanding of their possible harmful effects. However, no standard method has been established to measure microplastics and the measurement of microplastics has been done by various methods in different published studies. The aim of current study was to investigate different methods of measuring microplastics in water and wastewater environment and identifying the strengths and weaknesses of these methods. Materials and Methods: The present review study was conducted during the winter 2021, by searching the papers cited in PubMed, Google Scholar, Web of Science, and Scopus databases using the keywords "Microplastic", "Water", "Drinking-water", "Wastewater", "Surface", "Bottled-water" and "Marine" and selecting articles published between 2015 and 2021 in reputable journals. Results: The main stages of MPs measuring in various studies included sampling and sieving, pretreatment and digestion, density separation, counting and Identification of MPs by their chemical composition. Conclusion: Digestion using H2O2, density separation using NaCl, counting by stereomicroscope, and Spectroscopy using FTIR and micro-RAMAN are the most widely used methods in the studies related to detecting MPs in water and wastewater environment. However, different methods of measuring and identifying microplastics have made comparing the results of studies difficult and it seems that efforts should be made to standardize these methods.